Commissars and cars: A case study in the political economy of dictatorship. - Lazarev, Valery; Gregory, Paul (Journal of Comparative Economics, 2003)
We use unique archival data on the allocation of vehicles, i.e. cars and trucks, in the 1930s by a three-person commission of top Soviet officials for an empirical investigation of resource allocation by a dictatorship. Two distinct models of dictatorial allocative behavior, namely, an economic planning model and a political gift exchange model, are considered. We use censored regression and ordered probit to show that the political gift exchange model is supported strongly by the data, but the economic model is rejected. Moreover, the political model explains better the rejection of petitions rather than their success, suggesting that the dictator preferred unconstrained decision-making discretion. We argue that the dictator used gift exchange to purchase loyalty against uncontrolled market exchanges and that political bias in resource allocation was undermining the dictator's power in the long run. Copyright (c) 2003 Elsevier Science (USA)